The Impact of Andalusian Migration on Educational Life in the Central Maghreb during the Middle Ages - Benamara, Asma; Ahmed, Abdelraouf Zouari (Journal of Ecohumanism, 2026)
This study examines the impact of Andalusian migration on the development of educational life in the Central Maghreb during the Middle Ages against the backdrop of the political and military transformations experienced in al-Andalus as a result of the intensification of the Christian Reconquista, particularly after the defeat of the Almohads at the Battle of Las Navas de Tolosa in 609 AH/1212 CE. These circumstances led to the migration of large numbers of Andalusians to the lands of the Islamic Maghreb. The Central Maghreb received a significant share of these migratory movements owing to its geographical proximity to al-Andalus, the relative stability it offered, and the welcome extended to this community by the ruling authorities, such as the Zayyanid and Hafsid states. The Andalusians brought with them a substantial scholarly and cultural legacy that helped invigorate intellectual and scientific life in the urban centres of the Central Maghreb, especially in the field of education. Andalusian scholars also played a role in renewing educational curricula and teaching methods by introducing new fields of knowledge and adopting innovative pedagogical approaches. This, in turn, led to the flourishing of scholarly activity in cities such as Tlemcen, Bejaia, and Constantine and to the emergence of an elite group of scholars who played a prominent role in the development of cultural life in the Central Maghreb.